Majaz Isti’arah dalam Surah Yasin: Studi Pemikiran Ibn ‘Asyur dalam Kitab Al-Tahrir wa Al-Tanwir - Nurafika, Alfi; Niat, Khoirun; Aini, Nur (LPPM IIQ An Nur Yogyakarta, 2022)
Isti'arah is a pronunciation that is used inappropriately because of the 'alaqah in the form of imitation and the presence of qarinah that prevents from the original meaning. The principle of using isti'arah in the Qur'an aims to attract the attention of the listeners and readers of the Qur'an so that with the element of eloquence and the beauty of the words and meanings in it can touch the soul. This research focuses on how the isti'arah interpretation model of Ibn Asyur in Surah Yasin in the al-Tahrir wa al-Tanwir, as well as how he interprets the verses containing isti'arah in Surah Yasin, as well as the implications of the use of isti’arah on the interpretation of Ibn Asyur . The research method used is qualitative which leads to descriptive analysis, namely classifying verses that contain isti'arah and then explaining and analyzing their implications. The approach used is the balaghah science approach, precisely the science of parrots with data collection techniques through library research. From the results of the study it can be concluded that the interpretation model of Ibn Asyur's isti'arah includes three criteria, namely first, when interpreting the verse in the form of isti’rah, Ibn Asyur raises an explanation that the verse contains isti’?rah, either by using the word isti'arah or another sighat of isti'arah. Second, explain the type of isti'arah contained in the verse. Third, mention the meaning contained in the form of isti'arah in the verse. Then in Surah Yasin there are ten verses that contain isti'arah namely in the verse QS 8, 9, 11, 12, 29, 37, 52, 71, 74 and 78. The use of isti'arah in the Qur'an has implications for showing the superiority of the language of the Qur'an.